Appreciative Leadership and Teacher’s Subjective Well-being: An Appreciative Tool for an Appreciative Outcome - Bashaireh, Suhair (2019)
Educational scholars and reformers have reached a consensus on the importance of teacher’s well being in education. Teacher’s and student’s well-being can be considered two sides of the same coin. It is considered by a lot of researchers as an essential ingredient for building human capacity in a first-rate educational system. Therefore, the need to improve teacher’s well-being is essential within the education industry. However, teacher’s well-being is a broad concept governed by multiple variables. The effect of school leadership on teacher’s well-being has been under the microscope recently not only within educational research but also as part of well-being and organizational studies. This study examines the effect of Appreciative Leadership on teacher’s subjective well-being through the perspective of teachers (instructional and non-instructional staff). It uses a mixed method approach using both a qualitative and quantitative instrument. It also provides interventions to promote teacher’s well-being through Appreciative Inquiry (AI) 4-D cycle. The study targeted 94 instructional and non-instructional staff from different phases (K-12) in 4 schools in Dubai that has different KHDA rating. However, the Appreciative Inquiry Summit was delivered in one of those schools only for convenience issues. The current study consulted different theories that Appreciative Leadership is grounded in as social constructionism, Appreciative Inquiry, and positive psychology. The major results of the study indicate that Appreciative Leadership affect teacher’s subjective well-being at school. The positive core shared through the Appreciative Inquiry Summit indicates that Appreciative Leadership strategies and practices have a positive effect on teacher’s well-being. The Appreciative Inquiry summit produced several interventions designed collaboratively and positively by teachers and leaders to be delivered within schools to promote teacher’s well-being.